2015
DOI: 10.3109/07357907.2015.1036280
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Simplified Chinese Version of EORTC QLQ-HCC18 for Patients with Hepatocellular Carcinoma

Abstract: This study aimed to develop and validate the Simplified Chinese Version of the Quality of Life Questionnaire for Hepatocellular Carcinoma (the QLQ-HCC18). It was developed by the strict translation procedure of EORTC guidelines, and the psychometrics were evaluated on a sample of 114 patients. The internal consistency Cronbach's α were greater than 0.60 for all domains (exception of Jaundice 0.38), and all test-retest reliability coefficients were greater than 0.80. Four out of eight domains had statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…To our knowledge, the all-stage conceptual model developed in the current study is the first of its kind. Patients with BTC experience reduced HRQoL [19,36,37], and this was reflected in the current study. Patients with BTC mentioned 46 signs/symptoms and eight impacts of BTC that had not been identified from the targeted literature and clinician interviews, highlighting the importance of obtaining information on the patient experience directly from patients and suggesting a need to ensure fit-for-purpose patient-centred outcomes measurement in BTC clinical trials.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…To our knowledge, the all-stage conceptual model developed in the current study is the first of its kind. Patients with BTC experience reduced HRQoL [19,36,37], and this was reflected in the current study. Patients with BTC mentioned 46 signs/symptoms and eight impacts of BTC that had not been identified from the targeted literature and clinician interviews, highlighting the importance of obtaining information on the patient experience directly from patients and suggesting a need to ensure fit-for-purpose patient-centred outcomes measurement in BTC clinical trials.…”
Section: Discussionsupporting
confidence: 62%
“…No recent BTC-related qualitative research studies were identified from the literature review. Six non-qualitative studies were identified (two retrospective cohort studies and four prospective studies) [14,[32][33][34][35][36], and 19 concepts related to signs/symptoms or impacts of BTC were extracted from these and included in the preliminary conceptual model. These studies used validated questionnaires to assess patients' HRQoL in the physical, mental and social domains in the context of BTC [14,[32][33][34][35][36].…”
Section: Targeted Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, nine publications combined patient groups undergoing different treatment options (surgery/medical therapy/interventional treatment) for the reporting of HRQoL outcomes. In these cases, assignment of HRQoL outcomes to a specific treatment (surgery vs. medical therapy vs interventional treatment) was impossible [ 28 , 42 , 56 , 58 , 87 , 88 , 120 , 127 , 132 ]. In summary, only three studies remained for quantitative analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several different questionnaires have been employed to measure HRQoL in studies of HCC [7]; however, only the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Hepatocellular Carcinoma 18-question module (EORTC QLQ-HCC18) was developed speci cally to assess symptom burden and impact on HRQoL in people with HCC [12][13][14]. As it stands, there are limited published data demonstrating the measurement properties of the QLQ-HCC18 within an unresectable HCC population, as well as within speci c subpopulations including viral hepatitis comorbidities (comorbid HBV and HCV versus no comorbidity), line of therapy (second-versus third-line or greater), and geographic region (Asia versus Europe).…”
Section: Introductionmentioning
confidence: 99%